2014
DOI: 10.1186/s40694-014-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting the biodiversity of the fungal family Ustilaginaceae for the production of value-added chemicals

Abstract: BackgroundUstilaginaceae (belonging to the smut fungi) are commonly known for their plant pathogenicity. Although these microbes lead to yield reduction of cereal production, they can also have an economically positive side. Ustilaginaceae naturally produce a versatile range of value-added chemicals with potential applications in the food, pharmaceutical, and chemical industry.ResultsIn this study 68 Ustilaginaceae of 13 species were screened for the production of organic acids, polyols, and glycolipids from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
125
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 47 publications
8
125
0
5
Order By: Relevance
“…Total RNA was extracted from the respective strains grown in screening medium (21) supplemented with 20 g liter Ϫ1 glucose for 12 h using the Tri Reagent (Roth, Karlsruhe, Germany), according to the manufacturer's instructions. Ten micrograms of total RNA was treated with 2 U of DNase I (New England BioLabs, Frankfurt am Main, Germany) for 10 min at 37°C to remove residual genomic DNA and subsequently purified by phenol-chloroform extraction and sodium acetate precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Total RNA was extracted from the respective strains grown in screening medium (21) supplemented with 20 g liter Ϫ1 glucose for 12 h using the Tri Reagent (Roth, Karlsruhe, Germany), according to the manufacturer's instructions. Ten micrograms of total RNA was treated with 2 U of DNase I (New England BioLabs, Frankfurt am Main, Germany) for 10 min at 37°C to remove residual genomic DNA and subsequently purified by phenol-chloroform extraction and sodium acetate precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…As a plant pathogen, U. maydis possesses a limited but complete set of hydrolases that in theory enable the utilization of complex substrates, like cellulose, xylan, or pectin, for growth (21,38,43,44). However, transcription studies revealed that gene expression for most of these CAZymes is restricted to the phase of infection, when the fungus invades the plant and proliferates, while they are often dormant during the industrially relevant yeast-like growth (45).…”
mentioning
confidence: 99%
See 3 more Smart Citations